First-principles study of cubic BxGa1-xN alloys - Lachebi, A.; Abid, H.; Driz, M.; Al-Douri, Y. (Universiti Malaysia Perlis, 2008)
Link to publisher's homepage at http://www.unimap.edu.my/ ; Open access only applicable for vol. 1; issue 1, 2008.